On the evection resonance and its connection to the stability of outer satellites - Yokoyama, Tadashi [UNESP]; Neto, Ernesto Vieira [UNESP]; Winter, Othon Cabo [UNESP]; Sanchez, Diogo Merguizo [UNESP]; de Oliveira Brasil, Pedro Ivo [UNESP] (Hindawi Publishing Corporation, 2008)
In terms of stability around the primary, it is widely known that the semimajor axis of the retrograde satellites is much larger than the corresponding semimajor axis of the prograde satellites. Usually this conclusion is obtained numerically, since precise analytical derivation is far from being easy, especially, in the case of two or more disturbers. Following the seminal idea that what is unstable in the restricted three-body problem is also unstable in the general N-body problem, we present a simplified model which allows us to derive interesting resonant configurations. These configurations are responsible for cumulative perturbations which can give birth to strong instability that may cause the ejection of the satellite. Then we obtain, analytically, approximate bounds of the stability of prograde and retrograde satellites. Although we recover quite well previous results of other authors, we comment very briefly some weakness of these bounds. Copyright (c) 2008 Tadashi Yokoyama et al.